2013
DOI: 10.1093/humrep/det132
|View full text |Cite
|
Sign up to set email alerts
|

Tetraploidy in hydatidiform moles

Abstract: study question: How does tetraploidy develop in hydatidiform moles (HMs), and what is the frequency of the different origins? summary answer: Most molar pregnancies with tetraploid cells appear to be produced by somatic endoreduplications, while a minority originate from a tetraploid zygote. The frequency of zygotic tetraploidy was estimated to be 0.7%.what is known already: The parental origin of the genome in tetraploid HMs has only been evaluated in a few cases, most showing three genome sets from the fathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
(35 reference statements)
2
13
0
1
Order By: Relevance
“…The results of the DNA marker analysis corroborated this statement, since in several loci this pregnancy showed 2 different paternal alleles or 2 different maternal alleles or both. To our knowledge such karyotype has only been reported in 6 previous cases, 5 of them associated with partial hydatidiform moles, with a PPPM genotype (3 paternal (P) and 1 maternal (M) alleles) [Surti et al, 1986;Murphy et al, 2012;Sundvall et al, 2013]. The case of Baumer et al [2003] is similar to ours, with a PPMM genotype found in a spontaneously aborted embryo.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The results of the DNA marker analysis corroborated this statement, since in several loci this pregnancy showed 2 different paternal alleles or 2 different maternal alleles or both. To our knowledge such karyotype has only been reported in 6 previous cases, 5 of them associated with partial hydatidiform moles, with a PPPM genotype (3 paternal (P) and 1 maternal (M) alleles) [Surti et al, 1986;Murphy et al, 2012;Sundvall et al, 2013]. The case of Baumer et al [2003] is similar to ours, with a PPMM genotype found in a spontaneously aborted embryo.…”
Section: Resultssupporting
confidence: 76%
“…The finding of a complete tetraploidy in native trophoblast cells, evidenced by the CVS short-term culture, might be indicative of a 'zygotic tetraploidy' where all cells are tetraploid and derived from a tetraploid conceptus [Sundvall et al, 2013]. However, in viable pregnancies, complete tetraploidy in a trophoblast is not an infrequent finding and is usually confined to this tissue.…”
Section: Resultsmentioning
confidence: 93%
“…This leads to DNA replication without cell division, producing a tetraploid cell. Mosaic tetraploidy is observed in <1% of molar pregnancies [39], but may be more frequent at earlier embryonic stages. Indeed, some studies have suggested tetraploidy to be a normal feature of blastocyst-stage embryos [19].…”
Section: Molecular Factors Contributing To Mitotic Errormentioning
confidence: 99%
“…However, polyploid molar pregnancies generally show heterozygosity for paternal alleles. [12,13] Although we only had few informative loci, we did not observe heterozygosity for paternal markers making polyploidy unlikely. Increasing the number of loci analyzed could increase the validity of this conclusion.…”
Section: Discussionmentioning
confidence: 91%